Integration of Technological Curriculum Models and Academic Subjects; Efforts to Balance Digital Literacy and Depth of Material - Dinda Listia Ramadhani; Ahmad Hasyemi; Fannisa Naila Fitriani (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
The acceleration of digital education in Indonesia is currently confronted with the issue of a technology skills divide and conventional curriculum frameworks that tend to be theoretical-fragmentary. To anticipate these challenges, this study aims to conceptualize curriculum reconstruction through an eclectic-integrative approach to fully facilitate learners' multidimensional development. The methodology employs a qualitative approach with descriptive analysis techniques, utilizing a theoretical review of classical to contemporary curriculum models, an evaluation of the Kurikulum Merdeka policy, and case study explanations from both formal and non-formal educational institutions. The results confirm that the structural limitations of traditional and progressive design models can be bridged through the synchronization of horizontal and vertical organizational dimensions. This eclectic-integrative formula simultaneously unifies the strengths of academic orientation (subject-centered), humanization (learner-centered), and social problem resolution (problem-centered). Through a cohesive integration of instructional phases spanning the consolidation of scientific foundations, internalization of affective values, and execution of social actions this model proves highly accelerative in enhancing digital competence, aligning outcomes with the Profil Pelajar Pancasila, and fostering tangible community empathy. This study concludes that the eclectic-integrative pattern serves as a visionary, adaptive, and contextual curriculum foundation to reform the national educational landscape in the modern era.